A proposal which involves using indigenous learning systems to improve the quality of education in deprived communities - Barsaga, Eligio
The purpose of the research is to identify, develop and apply the methods of indigenous system, to provide improvements in the quality of education provided in deprived communities. The research activities can be divided into three areas: literature review, case studies and implementation studies.
Keywords: Indigenous peoples -- Education -- Philippines; Instructional systems -- Philippines; Teaching -- Philippines -- Aids and devices